Ginsenoside-Mc1 reduces cerebral ischemia-reperfusion injury in hyperlipidemia through mitochondrial improvement and attenuation of oxidative/endoplasmic reticulum stress - Wang, Min; Li, Danni (Archives of Biological Sciences, 2022)
Paper description: Neuroprotection in hyperlipidemic patients suffering from cerebral ischemia-reperfusion (I/RI) injury necessitates the use of safe and effective therapy. Ginsenoside compound Mc1 (GMc1) was effective in limiting cerebral infarct volumes in rats by attenuating mitochondrial-dependent oxidative/endoplasmic reticulum stress. The neuroprotective effect of GMc1 was achieved via activation of mitochondrial ATP-sensitive K channels. GMc1 preconditioning may be a promising strategy for improving the outcome of ischemic brain disease in hyperlipidemic patients. Abstract: The neuroprotective effect of ginsenoside-Mc1 (GMc1) in hyperlipidemic rats in the setting of cerebral ischemia-reperfusion injury (I/RI), as well as the role of mitochondrial ATP-sensitive potassium (mitoKATP) channels and oxidative/endoplasmic reticulum (ER) stress, was investigated. Hyperlipidemia (8 weeks) was induced by a high-fat diet in Sprague Dawley rats. GMc1 (10 mg/kg, i.p.) was given to hyperlipidemic rats daily for one month before I/RI. Rat brains were subjected to 2 h of local ischemia followed by 24 h reperfusion. The cerebral infarcted injury was measured by triphenyl-tetrazolium chloride staining and the levels of oxidative stress indicators were detected by ELISA and spectrophotometry. A fluorometric technique was employed to evaluate mitochondrial function. Western blotting was used to detect changes in the expression of ER stress proteins. GMc1 reduced cerebral infarct volume in hyperlipidemic rats in comparison to untreated ones (P<0.01). GMc1 reduced cerebral infarct volume in hyperlipidemic rats as compared to untreated rats (P<0.01). GMc1 significantly decreased mitochondrial membrane depolarization, mitochondrial reactive oxygen species (mitoROS) and malondialdehyde levels (P<0.01), while increasing the activity of superoxide dismutase (SOD), catalase (CAT) and glutathione-peroxidase (GPx) (P<0.001). GMc1 administration reduced the expression of ER stress markers, including phosphorylated (p)-endoplasmic reticulum kinase (PERK), p-eukaryotic translation initiation factor 2 subunit 1 (elF2α), and C/EBP homologous protein (CHOP). Inhibition of mitoKATP channels with hydroxydecanoate significantly eliminated the protective impacts of GMc1 in hyperlipidemic rats subjected to cerebral I/RI. The neuroprotective effect of GMc1 preconditioning was remarkably improved by increasing mitoKATP channel activity and decreasing oxidative and ER stress levels in hyperlipidemic rats, implying that this compound could be an appropriate candidate for reducing cerebral I/RI in comorbidities.